The accumulation of strontium by native plants grown on Gumuskoy mining soils - Sasmaz, Merve; Sasmaz, Ahmet (Elsevier Science Bv, 2017)
The Giirniiskoy mining area is located about 25 km west of Kiltahya and the largest silver deposit in Turkey. The present study investigated the translocation and accumulation of Sr from the Gtimii koy mining soils into 11 native plants. Plant and soil samples were collected from the field, and Sr concentrations were analyzed by ICP-MS. The average Sr values in the soil, root, and shoot of the native plants in the study area were 148.55, 163.65, and 163.93 ppm, respectively. The plants were separated to several groups (the best plants, good plant and candidate plants) according to ECS and ECR values of these plants. These groups showed that the best plants; Carduus nutans, Onosma sp., Alyssum saxatile, Anchusa arvensis and Centaurea cyanus, good plants; Verbascum thapsus, Isatis, Phlomis sp., Cynoglossum officinale and Glaucium flavum and candidate plants; Silene compacta for Sr. The present study revealed that both the best and good plants in the study area had very high potential to remove Sr, Therefore, these plants can be useful for remediation or phytoremediation studies of soils polluted by Sr.
Keywords: Accumulation; Mining area; Native plant; Strontium; Phytoremediation